All Days 2010
DOI: 10.2118/128066-ms
|View full text |Cite
|
Sign up to set email alerts
|

Formation Damage and Impact on Gas Flow Caused by Biofilms Growing Within Proppant Packing Used in Hydraulic Fracturing

Abstract: Formation damage as a result of hydraulic fracturing of unconventional gas reservoirs is known to occur by many speculated processes such as: filter cakes on fracture faces, matrix swelling, cleat plugging, gel damage and water blocking. In low permeability matrices, capillary forces can also prevent effective dewatering and result in water blocking of gas flow. Another type of formation damage that may be qualitatively understood but not quantified is the impact of biofilms. This paper combines two micro-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…The Halanaerobium MAGs recovered from unconventional reservoirs contained genes encoding proteins involved with the biofilm formation process ( Daly et al, 2016 ; Lipus et al, 2017 ). Microbial biofilms are a major issue in the oil and gas industry, as they can lead to clogging and increase the rates and/or severity of MIC ( Johnson et al, 2008 ; Bottero et al, 2010 ; Struchtemeyer et al, 2012 ). Pseudomonas are especially well known due to their biofilm formation capabilities ( Drenkard and Ausubel, 2002 ; Vikram et al, 2015 ) and have been shown to increase biofilm production when exposed to produced water ( Vikram et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Halanaerobium MAGs recovered from unconventional reservoirs contained genes encoding proteins involved with the biofilm formation process ( Daly et al, 2016 ; Lipus et al, 2017 ). Microbial biofilms are a major issue in the oil and gas industry, as they can lead to clogging and increase the rates and/or severity of MIC ( Johnson et al, 2008 ; Bottero et al, 2010 ; Struchtemeyer et al, 2012 ). Pseudomonas are especially well known due to their biofilm formation capabilities ( Drenkard and Ausubel, 2002 ; Vikram et al, 2015 ) and have been shown to increase biofilm production when exposed to produced water ( Vikram et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively biogenic sulfide can also result from the transfer of reducing equivalents onto thiosulfate during fermentation reactions (Booker et al, 2017). Additionally, the formation of microbial biofilms may impede gas flow and result in fracture clogging (Bottero et al, 2010). Evidence suggests that organic chemicals used during hydraulic fracturing may stimulate these deleterious processes, for example via organic acid production from fermentation reactions, and sulfide production from sulfate and thiosulfate reduction pathways (Struchtemeyer et al, 2011;Liang et al, 2016;Booker et al, 2017Booker et al, , 2019Nixon et al, 2017;Evans et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Increased corrosion risk is another reason why the production of sulfide should be avoided. In addition, it has been suggested that microbial growth downhole may cause plugging, preventing the free flow of gas from freshly fractured wells (Bottero et al, 2010). Production of shale oil can similarly be affected by souring caused by the activity of SRB and associated corrosion.…”
Section: Introductionmentioning
confidence: 99%